Method for measuring reaction rate constant of active particles of lithium ion battery

By using a single-layer particle electrode and Li||Li symmetric battery measurement method in lithium-ion batteries, combined with the Butler-Volmer equation, the problem of insufficient measurement accuracy in the prior art is solved, and high accuracy measurement of the reaction rate constant of the active particles of lithium-ion batteries is achieved.

CN119688535AActive Publication Date: 2025-03-25HUAZHONG UNIV OF SCI & TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411870697.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-03-25
Estimated Expiration
2044-12-18

AI Technical Summary

Technical Problem

The existing methods for measuring the reaction rate constant of active particles of lithium-ion batteries have problems such as insufficient accuracy, long testing time and strong dependence on electrode materials, and it is difficult to accurately reflect the reaction characteristics of individual particles.

Method used

A single-layer particle electrode structure is used to measure the lithium metal reaction overpotential and liquid phase transmission overpotential through Li||Li symmetrical battery, and the reaction rate constant is calculated based on the Butler-Volmer equation, and the difference in the surface and internal lithium ion concentrations of active particles is considered to improve the accuracy of measurement.

Benefits of technology

It improves the accuracy and efficiency of reaction rate constant measurement, can more accurately reflect the reaction characteristics of individual active particles, and helps optimize the performance of lithium-ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119688535A_ABST
    Figure CN119688535A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field related to electrochemical testing, and discloses a lithium ion battery active particle reaction rate constant measuring method, which comprises the following steps: (1) carrying out particle size distribution test on active material powder to be measured, and then calculating the current density of a reaction interface; meanwhile, analyzing a discharge-relaxation curve of the LiLi symmetric battery, and further calculating liquid-phase lithium ion concentration distribution; (2) analyzing a discharge-relaxation curve of the single-layer particle battery, and further calculating the characteristic time and the charge transfer overpotential of the charge transfer process; (3) taking charge transfer process response time and liquid-phase transmission overpotential into consideration, adding relaxation overpotential at characteristic time corresponding to charge transfer to the liquid-phase transmission overpotential to obtain solid-phase equilibrium potential, and then reversely solving the solid-phase lithium ion concentration in combination with the measured open-circuit voltage curve; and (4) substituting the obtained related parameters into a Butler-Volmer equation, and calculating to obtain a reaction rate constant. According to the invention, the accuracy is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field related to electrochemical testing, and more specifically, relates to a method for measuring the reaction rate constant of active particles of a lithium ion battery. Background Art

[0002] As a high-efficiency secondary battery, lithium-ion batteries have been widely used in consumer electronics, transportation and large-scale energy storage. With the continuous improvement of energy density, power density and cycle life, the performance optimization of lithium-ion batteries has become a hot topic in electrochemical research. However, the overall performance of the battery not only depends on the selection of materials, but is also significantly affected by the electrode reaction kinetics. In particular, the reaction rate constant of the active particles in the electrode material directly determines the insertion and deinsertion speed of lithium ions, thereby affecting the battery's charge and discharge rate, energy conversion efficiency and thermal management performance.

[0003] Most existing methods for measuring the reaction rate constants of active particles in lithium-ion batteries rely on technologies such as electrochemical impedance spectroscopy (EIS) and constant current charge and discharge tests. However, these methods often have problems such as insufficient accuracy, long test time, and strong dependence on electrode materials when faced with particle-level kinetic behavior. In addition, due to the large diversity in the size and morphology of active particles in electrode materials, traditional methods have difficulty distinguishing the differences between particles, resulting in the data obtained being unable to accurately reflect the reaction characteristics of individual particles. This poses a challenge to battery design and optimization, especially when pursuing high-rate performance and long-life cycles, the limitations of traditional measurement methods become more obvious. Summary of the invention

[0004] In view of the above defects or improvement needs of the prior art, the present invention provides a method for measuring the reaction rate constant of active particles in lithium ion batteries, which aims to solve the problem of low accuracy of the existing method for measuring the reaction rate constant of active particles in lithium ion batteries.

[0005] To achieve the above object, according to one aspect of the present invention, a method for measuring the reaction rate constant of active particles in a lithium ion battery is provided, characterized in that the method comprises the following steps:

[0006] (1) The active material powder to be measured is subjected to a particle size distribution test, and then the total reaction interface area of ​​the single-layer particle battery is calculated according to the electrode weight and electrode formula of the single-layer particle electrode and the battery capacity of the single-layer particle battery, and the reaction interface current density is calculated by dividing the applied current by the total area; at the same time, the discharge-relaxation curve of the Li||Li symmetric battery is analyzed, and the liquid phase transmission overpotential and the lithium metal charge transfer overpotential are resolved according to the response time, and the liquid phase lithium ion concentration distribution is calculated in combination with the liquid phase charge conservation equation; wherein the raw materials for preparing the single-layer particle electrode include the active material powder, and the single-layer particle battery uses the single-layer particle electrode as the positive electrode; the lithium sheet and the separator used in the Li||Li symmetric battery are the same as those of the single-layer particle battery;

[0007] (2) Analyze the discharge-relaxation curve of the single-layer particle battery, calculate the characteristic time of the charge transfer process based on the DRT analysis results of the EIS test, and then combine the response time to resolve the charge transfer overpotential on the electrode side;

[0008] (3) Considering the response time of the charge transfer process and the liquid phase transmission overpotential, the solid phase equilibrium potential is obtained by adding the relaxation overpotential at the characteristic time corresponding to the charge transfer to the liquid phase transmission overpotential, and then combined with the measured open circuit voltage curve to inversely solve the solid phase lithium ion concentration;

[0009] (4) Substitute the obtained reaction interface current density, liquid phase lithium ion concentration, charge transfer overpotential and solid phase lithium ion concentration into the Butler-Volmer equation to calculate the reaction rate constant.

[0010] Furthermore, the lithium ion concentration at the separator-electrode interface is equivalent to the lithium ion concentration in the liquid phase of the reaction interface of the single-layer particle battery, and the corresponding calculation formula is:

[0011]

[0012] Where R is the gas constant; T is the Kelvin temperature; t + is the ion transfer number; F is the Faraday constant; c l is the liquid lithium ion concentration; x is the position of the particle.

[0013] Furthermore, the calculation formula corresponding to the reaction rate constant is:

[0014]

[0015] Where k is the reaction rate constant; i loc is the local current density; i0 is the reference exchange current density; α a is the anode transfer coefficient; η is the charge transfer overpotential; F is the Faraday constant; R is the gas constant; T is the Kelvin temperature; α cis the cathode transfer coefficient; c s is the solid phase lithium ion concentration; c s,max is the maximum lithium insertion concentration in the solid phase; c l is the liquid phase lithium ion concentration.

[0016] Furthermore, the active material powder to be measured is coated into a single-layer particle electrode with excellent conductive properties, the conductive agent content in the slurry is greater than 10wt% of the total solid material mass, and the coating spacing used is greater than the diameter of the active material powder.

[0017] Furthermore, the solid content of the slurry of the single-layer particle electrode is in the range of 30wt% to 50wt%.

[0018] Furthermore, the drying method after coating is infrared heating, with a temperature of 50° C. to 70° C. and a time of 6 hours to 8 hours.

[0019] Furthermore, the small rate is selected as 0.2C, the charge is 3 times, the time resolution is selected as 1ms, the discharge rate can be selected as 0.1C, the single discharge time is 10 minutes to 30 minutes, and the relaxation time is twice the discharge time.

[0020] Furthermore, the sampling time of the relaxation instant is 1 ms.

[0021] Furthermore, the liquid phase overpotential and charge transfer overpotential are distinguished according to the speed of the response process. The potential that responds quickly at the relaxation moment jumps to the charge transfer overpotential of the lithium metal reaction, and the overpotential that recovers slowly after relaxation is the liquid phase transmission overpotential.

[0022] Furthermore, the open circuit voltage curves were obtained from the continuous discharge-relaxation tests according to the theoretical charge capacity.

[0023] In general, compared with the prior art, the above technical solution conceived by the present invention has the following beneficial effects:

[0024] 1. The present invention uses a single-layer particle electrode structure to eliminate the influence of the solid-liquid phase lithium ion concentration and the interface current density distribution in the thickness direction, so that the interface current distribution is uniform and the average value can be used for equivalence. When refined particles are used, the error will be further reduced, thereby improving the accuracy.

[0025] 2. The present invention measures the lithium metal reaction overpotential and liquid phase transmission overpotential through a Li||Li symmetric battery, the diaphragm state and lithium metal reaction overpotential in an equivalent single-layer particle battery, improves the accuracy of measuring the active particle charge transfer overpotential, and accurately measures the liquid phase lithium ion concentration.

[0026] 3. The present invention takes into account the difference in lithium ion concentration between the surface and interior of active particles, and calculates the accurate solid surface equilibrium potential in combination with the liquid phase transmission overpotential, thereby achieving real-time and accurate measurement of the solid phase lithium ion concentration at the reaction interface and avoiding the use of average values ​​for substitution.

[0027] 4. The present invention accurately determines the characteristic time corresponding to the charge transfer process through the results of DRT analysis, ensures that the charge transfer process is extracted, and eliminates the influence of the lithium metal reaction overpotential through the equivalent method. The electron transmission path is shortened through the single-layer particle electrode, and a large amount of conductive agent is added to improve the conductivity of the conductive network, thereby further improving the accuracy of the charge transfer overpotential measurement. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 It is a flow chart of a method for measuring the reaction rate constant of active particles of a lithium ion battery provided by the present invention;

[0029] Figure 2 a, b, and c are respectively schematic diagrams of the physical meanings of various parameters of the reaction interface involved in the present invention;

[0030] Figure 3 a, b, c, and d are schematic diagrams of the high-precision reaction rate constant calculation method involved in an embodiment of the present invention;

[0031] Figure 4 a and b are respectively a schematic diagram of an EIS test and a schematic diagram of a DRT analysis involved in an embodiment of the present invention;

[0032] Figure 5 It is a DRT analysis diagram corresponding to different SOCs involved in the embodiment of the present invention;

[0033] Figure 6 a and b are respectively single discharge-relaxation process analysis diagrams involved in the embodiments of the present invention;

[0034] Figure 7 is a graph showing the particle size distribution of the graphite material involved in the embodiment of the present invention;

[0035] Figure 8 a and b are comparative schematic diagrams of a scanning electron microscope image and a copper foil scanning image of a single-layer graphite electrode according to an embodiment of the present invention, respectively;

[0036] Fig. 9 is a graph showing the graphite reaction rate constant results obtained in an embodiment of the present invention;

[0037] Fig.10 a and b are comparison results of voltage and current density using the method provided by the present invention, the experiment and GITT respectively. DETAILED DESCRIPTION

[0038] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. In addition, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.

[0039] The present invention provides a method for measuring the reaction rate constant of active particles in a lithium ion battery. The method solves the reaction rate constant for the Butler-Volmer kinetic equation, and accurately solves the parameters designed by the Butler-Volmer equation one by one to obtain the correct reaction rate constant of the material. The structure of the single-layer particle electrode ensures uniform distribution of the concentration, current density, etc. in the thickness direction of the electrode, and the liquid phase lithium ion concentration on the diaphragm-electrode side can be equivalent to the interface concentration, and the average current density can be equivalent to the local interface current density; the Li||Li symmetric battery structure calculates the lithium metal reaction overpotential and liquid phase overpotential through high-resolution measurement of discharge-relaxation, and further calculates the liquid phase lithium ion concentration distribution according to the concentrated solution theory; the DRT analysis of the EIS test of the single-layer particle battery is combined to calculate the characteristic time of the charge transfer process, thereby extracting the correct charge transfer overpotential and solid phase surface open circuit voltage, and finally converting them into the interface solid phase lithium ion concentration; the particle size distribution results measured by the current average and particle size distribution instrument are combined and substituted into the Butler-Volmer equation to calculate the correct reaction rate constant.

[0040] See also Figure 1 , the measuring method mainly comprises the following steps:

[0041] Step 1: Perform a particle size distribution test on the active material powder to be measured, and then calculate the total reaction interface area of ​​the single-layer particle battery according to the electrode weight and electrode formula of the single-layer particle electrode and the battery capacity of the single-layer particle battery, and calculate the reaction interface current density by dividing the applied current by the total area; at the same time, analyze the discharge-relaxation curve of the Li||Li symmetric battery, resolve the liquid phase transmission overpotential and the lithium metal charge transfer overpotential according to the response time, and calculate the liquid phase lithium ion concentration distribution in combination with the liquid phase charge conservation equation; wherein, the raw materials for preparing the single-layer particle electrode include the active material powder, and the single-layer particle battery uses the single-layer particle electrode as the positive electrode; the lithium sheet and the separator used in the Li||Li symmetric battery are the same as those of the single-layer particle battery.

[0042] Among them, the active material powder to be measured is coated into a single-layer granular electrode plate with excellent conductive properties. It is necessary to ensure that the conductive agent content in the slurry is greater than 10wt% of the total solid material mass, and the coating spacing used must be only slightly larger than the diameter of the active material powder to ensure that the coated plate has only a single layer of active particles.

[0043] The obtained single-layer particle electrode sheet is made into a battery, and a lithium sheet is selected as the counter electrode, hereinafter referred to as a single-layer particle battery; at the same time, a Li||Li symmetric battery structure is prepared, and the lithium sheet and separator used are the same as the single-layer particle battery prepared previously.

[0044] After the single-layer particle battery is cycled multiple times at a small rate, continuous discharge-relaxation measurements are performed on a time high-resolution measuring instrument. The discharge rate is no more than 0.1C, and the single discharge time is greater than 5 minutes. It is then relaxed, and high-resolution sampling is performed from the moment of relaxation for more than 5 seconds. The same test is performed on the Li||Li symmetric battery at the same time.

[0045] The single-layer particle battery is charged to 1.5V at a small constant current rate, and then multiple EIS tests are carried out continuously to find the characteristic time corresponding to the charge transfer process, extract the correct charge transfer overpotential and open circuit voltage curve from the extracted discharge-relaxation curve, and calculate the liquid phase lithium ion concentration, solid phase lithium ion concentration and reaction current density at the interface.

[0046] In this embodiment, the solid content of the slurry of the single-layer particle electrode is in the range of 30wt% to 50wt%; the drying method after coating is infrared heating, the temperature is 50℃ to 70℃, and the time is 6 hours to 8 hours; the small rate is 0.2C, the formation is 3 times, the time resolution is 1ms, the discharge rate can be selected as 0.1C, the single discharge time is 10 minutes to 30 minutes, and the relaxation time is twice the discharge time; the DRT analysis used for EIS data can use the online tool package DRT tools.

[0047] The SEM scanned images can be used to confirm whether the electrode structure is qualified and calculate the total area of ​​the reaction interface.

[0048] The lithium ion concentration at the diaphragm-electrode interface is equivalent to the liquid phase lithium ion concentration at the reaction interface of the single-layer particle battery, and the corresponding calculation formula is:

[0049]

[0050] Where R is the gas constant; T is the Kelvin temperature; t + is the ion transfer number; F is the Faraday constant; c l is the liquid lithium ion concentration; x is the position of the particle.

[0051] Step 2: Analyze the discharge-relaxation curve of the single-layer particle battery, calculate the characteristic time of the charge transfer process based on the DRT analysis results of the EIS test, and then combine the response time to resolve the charge transfer overpotential on the electrode side.

[0052] The shorter the sampling time at the relaxation moment, the better. The best effect can be achieved at about 1ms. The liquid phase overpotential and charge transfer overpotential are distinguished according to the speed of the response process. The potential that responds quickly at the relaxation moment jumps to the charge transfer overpotential of the lithium metal reaction, and the overpotential that recovers slowly after relaxation is the liquid phase transmission overpotential.

[0053] DRT analysis can be performed using the online toolkit DRT tools, which can be used to determine the corresponding process based on the characteristic time and impedance size of each peak and the changes with SOC.

[0054] Step three, considering the response time of the charge transfer process and the liquid phase transmission overpotential, the solid phase equilibrium potential is obtained by adding the relaxation overpotential at the characteristic time corresponding to the charge transfer plus the liquid phase transmission overpotential, and then combined with the measured open circuit voltage curve to inversely solve the solid phase lithium ion concentration.

[0055] Among them, the open circuit voltage curve is obtained from continuous discharge-relaxation tests based on the theoretical charge capacity.

[0056] Step 4: Substitute the obtained reaction interface current density, liquid phase lithium ion concentration, charge transfer overpotential and solid phase lithium ion concentration into the Butler-Volmer equation to calculate the reaction rate constant.

[0057] The calculation formula for the reaction rate constant is:

[0058]

[0059] Where k is the reaction rate constant; i loc is the local current density; i0 is the reference exchange current density; α a is the anode transfer coefficient; η is the charge transfer overpotential; F is the Faraday constant; R is the gas constant; T is the Kelvin temperature; α c is the cathode transfer coefficient; c s is the solid phase lithium ion concentration; c s,max is the maximum lithium insertion concentration in the solid phase; c l is the liquid phase lithium ion concentration.

[0060] The present invention is further described in detail below with reference to specific embodiments.

[0061] In this embodiment, the positive and negative active materials of the single-layer particle electrode lithium-ion battery are graphite and lithium sheets, respectively, the positive electrode current collector material is copper, the diaphragm material is polyethylene, and the electrolyte material is LiPF6 dissolved in a solvent formed by mixing EC, DMC and EMC in a ratio of 1:1:1. The positive and negative electrodes of the Li||Li symmetrical battery use the same lithium sheets as the single-layer graphite electrode, and the diaphragm is also the same.

[0062] The specific steps are:

[0063] Step 1: Use graphite (Gr) active particles to prepare a single-layer particle electrode. The binder is carboxymethyl cellulose (CMC) and styrene-butadiene rubber (SBR), the conductive agent is conductive carbon black (SuperP), the solvent is deionized water, and the mass ratio of Gr, CMC, SuperP, SBR and deionized water is 6:1:2:1:20, a total of 3g. First, add CMC and SuperP together to half of the total amount of deionized water solvent and stir for 30 minutes to form a uniform colloidal solution at a rate of 500r / min. Then add Gr to the colloidal solution, add the other half of deionized water, stir at 700r / min for 5h, and finally add SBR to the colloidal solution, stir at 600r / min for 1h to obtain electrode slurry. Then use an infrared drying flat plate coating machine to coat the electrode slurry on aluminum foil, and adjust the coating gap to 20um. Finally, dry the electrode piece by infrared drying at 70°C for 6h to obtain a single-layer graphite electrode.

[0064] Step 2: The prepared single-layer ultra-thin electrode was cut into small discs (12 mm in diameter) by a slicer and assembled into a 2032-type button cell (Gr||Li) in a glove box filled with argon atmosphere. A lithium sheet (15.4 mm in diameter) was used as the counter electrode, and Celgard 2500 (18 mm in diameter) was used as the separator. 70 μl of electrolyte (1M LiPF.EC / EMC / DMC 1:1:11.0% VC) was added. At the same time, a Li||Li symmetric cell was assembled, using the same lithium sheet and separator, and adding the same amount of the same electrolyte.

[0065] Step 3: Calculate the reaction rate constant. All physical quantities that need to be measured and their meanings are as follows: Figure 2 As shown, it includes charge transfer overpotential, solid phase lithium ion concentration, liquid phase lithium ion concentration, and local current density at the reaction interface. The solution method is as follows Figure 3 After the single-layer graphite electrode was cycled 3 times at 0.2C, multiple EIS tests were performed on a Gamry interface 1010 electrochemical workstation, with the ambient temperature kept at 25°C and the test frequency ranging from 0.1Hz to 10 6Hz, 10 points are sampled for each order of magnitude, and after each test, 0.1C current is added to charge for 30 minutes, followed by relaxation for 1 hour to test the equilibrium potential, and the cycle is repeated multiple times until the potential after relaxation reaches 5mV or below. The results of the EIS test are imported into DRT tools for automated analysis and fitting. EIS test fitting and DRT analysis are as follows Figure 4 As shown, the DRT analysis results gamma vs tau corresponding to different SOCs are derived, and the characteristic time corresponding to the charge transfer process is determined according to the change of SOC and the relative size of impedance, as shown in Figure 5 As shown, from Figure 5 It can be seen that the peak that changes significantly with SOC is peak 5, and its corresponding characteristic time is about 0.3s.

[0066] Step 4: Clamp the single-layer graphite battery onto the LANHE test system (LANHE M340A) for testing, ensure that the ambient temperature is constant at 25°C, apply 0.1C current to discharge for 0.5h, then use 1ms high resolution to measure the temperature change in the first 5s of relaxation, and continue to relax for 1h after the end, and repeat multiple times until the voltage after relaxation is less than 5ms. Perform the same test 10 times with the same current density for the Li||Li symmetric battery. The analysis process of a single pulse is shown in Figure 6 First, the voltage jump value is extracted according to the characteristic time extracted above, which is the sum of the charge transfer overpotential of graphite and the charge transfer overpotential of lithium metal. Distinguishing the Lithium Metal Charge Transfer Overpotential η from the Rate of Voltage Jump in a Li||Li Symmetric Cell Li =1.582×10 -3 V and liquid diffusion overpotential η l =6.761×10 -3 V, subtract the lithium metal charge transfer overpotential from the sum of the graphite monolayer particle battery overpotentials extracted above to obtain the graphite charge transfer overpotential η ct =1.877×10 -3 V, substitute into the liquid phase charge conservation equation:

[0067]

[0068] The concentration of liquid lithium ions at the interface c l =999.8mol / m 3 .

[0069] Step 5: Place Gr powder in an electric blast drying oven at 70°C for 12 hours, and then fully dry it before performing a particle size distribution test. The experimental equipment used is Mastersizer 3000. The test results of the particle size distribution instrument are as follows: Figure 7The average particle size is calculated by volume fraction weighting, which is 6.4um. The SEM image of the surface of the Gr single-layer ultra-thin electrode sheet is obtained to confirm whether the correct single-layer electrode structure is obtained, such as Figure 8 As shown, it can be considered that the correct single-layer isolated particle structure is obtained. According to the total capacity of the battery, the total mass is divided by 340mAh / g, and the total interface area is calculated by the specific capacity of the 6.4um spherical particles. The local average current density is calculated by dividing the total interface area by the total external current density: 0.1918A / m 2

[0070] Step 6: Calculate the interface surface equilibrium potential. Substituting the open circuit voltage curve into Figure 2 The inverse solution is SOC = 0.311, which can be substituted into equation (2) and (3) to obtain k = 4.98 × 10 -11 m / s, the above method is substituted into the continuous discharge-relaxation curve to obtain multiple values ​​and plot them into a graphite reaction rate constant diagram, such as Fig. 9 shown.

[0071] since Fig.10 It can be seen that the measurement method provided by the present invention has achieved better technical effects, especially higher consistency with experimental results.

[0072] It will be easily understood by those skilled in the art that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for measuring the reaction rate constant of active particles in a lithium ion battery, characterized in that: The method comprises the following steps: (1) The active material powder to be measured is subjected to a particle size distribution test, and then the total reaction interface area of ​​the single-layer particle battery is calculated according to the electrode weight and electrode formula of the single-layer particle electrode and the battery capacity of the single-layer particle battery, and the reaction interface current density is calculated by dividing the applied current by the total area; at the same time, the discharge-relaxation curve of the Li||Li symmetric battery is analyzed, and the liquid phase transmission overpotential and the lithium metal charge transfer overpotential are resolved according to the response time, and the liquid phase lithium ion concentration distribution is calculated in combination with the liquid phase charge conservation equation; wherein the raw materials for preparing the single-layer particle electrode include the active material powder, and the single-layer particle battery uses the single-layer particle electrode as the positive electrode; the lithium sheet and the separator used in the Li||Li symmetric battery are the same as those of the single-layer particle battery; (2) Analyze the discharge-relaxation curve of the single-layer particle battery, calculate the characteristic time of the charge transfer process based on the DRT analysis results of the EIS test, and then combine the response time to resolve the charge transfer overpotential on the electrode side; (3) Considering the response time of the charge transfer process and the liquid phase transmission overpotential, the solid phase equilibrium potential is obtained by adding the relaxation overpotential at the characteristic time corresponding to the charge transfer to the liquid phase transmission overpotential, and then combined with the measured open circuit voltage curve to inversely solve the solid phase lithium ion concentration; (4) Substitute the obtained reaction interface current density, liquid phase lithium ion concentration, charge transfer overpotential and solid phase lithium ion concentration into the Butler-Volmer equation to calculate the reaction rate constant.

2. The method for measuring the reaction rate constant of active particles of a lithium ion battery according to claim 1, characterized in that: The lithium ion concentration at the separator-electrode interface is equivalent to the liquid phase lithium ion concentration at the reaction interface of a single-layer particle battery, and the corresponding calculation formula is: Where R is the gas constant; T is the Kelvin temperature; t + is the ion transfer number; F is the Faraday constant; c l is the liquid lithium ion concentration; x is the position of the particle.

3. The method for measuring the reaction rate constant of active particles of a lithium ion battery according to claim 1, characterized in that: The calculation formula for the reaction rate constant is: Where k is the reaction rate constant; i loc is the local current density; i0 is the reference exchange current density; α a is the anode transfer coefficient; η is the charge transfer overpotential; F is the Faraday constant; R is the gas constant; T is the Kelvin temperature; α c is the cathode transfer coefficient; c s is the solid phase lithium ion concentration; c s,max is the maximum lithium insertion concentration in the solid phase; c l is the liquid phase lithium ion concentration.

4. The method for measuring the reaction rate constant of active particles of a lithium ion battery according to claim 1, characterized in that: The active material powder to be measured is coated into a single-layer particle electrode with excellent conductive properties, the conductive agent content in the slurry is greater than 10wt% of the total solid material mass, and the coating spacing used is greater than the diameter of the active material powder.

5. The method for measuring the reaction rate constant of active particles of a lithium ion battery according to claim 4, characterized in that: The solid content of the slurry of the single-layer particle electrode is in the range of 30wt% to 50wt%.

6. The method for measuring the reaction rate constant of active particles of a lithium ion battery according to claim 4, characterized in that: The drying method after coating is infrared heating, the temperature is 50°C to 70°C, and the time is 6 hours to 8 hours.

7. The method for measuring the reaction rate constant of active particles of a lithium ion battery according to any one of claims 1 to 6, characterized in that: Select 0.2C for the minimum rate, 3 times for formation, 1ms for the time resolution, 0.1C for the discharge rate, 10 to 30 minutes for the single discharge time, and the relaxation time is twice the discharge time.

8. The method for measuring the reaction rate constant of active particles of a lithium ion battery according to any one of claims 1 to 6, characterized in that: The sampling time of the relaxation instant is 1 ms.

9. The method for measuring the reaction rate constant of active particles of a lithium ion battery according to any one of claims 1 to 6, characterized in that: The liquid phase overpotential and charge transfer overpotential are distinguished according to the speed of the response process. The potential that responds quickly at the moment of relaxation jumps to the charge transfer overpotential of the lithium metal reaction, and the overpotential that recovers slowly after relaxation is the liquid phase transmission overpotential.

10. The method for measuring the reaction rate constant of active particles of a lithium ion battery according to any one of claims 1 to 6, characterized in that: The open circuit voltage curves were obtained from successive discharge-relaxation tests based on the theoretical charge capacity.

Citation Information

Patent Citations

  • Method for evaluating lithium ion diffusion rate based on GITT test

    CN118938035A

  • Analysis of substance concentration in fluid sample

    DE19736156A1

  • Secondary battery

    KR1020240060775A